Mitochondrial involvement in memory impairment induced by scopolamine in rats. (3rd July 2017) - Wong-Guerra, Maylin; Jiménez-Martin, Javier; Pardo-Andreu, Gilberto L.; Fonseca-Fonseca, Luis A.; Souza, Diogo O.; de Assis, Adriano M.; Ramirez-Sanchez, Jeney; del Valle, Roberto Menéndez-Soto; Nuñez-Figueredo, Yanier
Abstract: Objective: Scopolamine (SCO) administration to rats induces molecular features of AD and other dementias, including impaired cognition, increased oxidative stress, and imbalanced cholinergic transmission. Although mitochondrial dysfunction is involved in different types of dementias, its role in cognitive impairment induced by SCO has not been well elucidated. The aim of this work was to evaluate the in vivo effect of SCO on different brain mitochondrial parameters in rats to explore its neurotoxic mechanisms of action. Methods: Saline (Control) or SCO (1 mg/kg) was administered intraperitoneally 30 min prior to neurobehavioral and biochemical evaluations. Novel object recognition and Y-maze paradigms were used to evaluate the impact on memory, while redox profiles in different brain regions and the acetylcholinesterase (AChE) activity of the whole brain were assessed to elucidate the amnesic mechanism of SCO. Finally, the effects of SCO on brain mitochondria were evaluated both ex vivo and in vitro, the latter to determine whether SCO could directly interfere with mitochondrial function. Results: SCO administration induced memory deficit, increased oxidative stress, and increased AChE activities in the hippocampus and prefrontal cortex. Isolated brain mitochondria from rats administered with SCO were more vulnerable to mitochondrial swelling, membrane potential dissipation, H2 O2 generation and calcium efflux, all likely resulting from oxidative damage. The in vitro mitochondrial assays suggest that SCO did not affect the organelle function directly. Conclusion: In conclusion, the present results indicate that SCO induced cognitive dysfunction and oxidative stress may involve brain mitochondrial impairment, an important target for new neuroprotective compounds against AD and other dementias.